Aerodynamic interaction between in-line runners: new insights on the drafting strategy in running - Beaumont, Fabien; Legrand, Fabien; Bogard, Fabien; Murer, Sébastien; Vernede, Victor; Polidori, Guillaume (Sports Biomechanics, 2021)
This study aims at modelling the aerodynamic interaction between a world-class runner and several pacers running in line, the objective being to determine the best drafting position in terms of potential speed gain and running time. Computational Fluid Dynamics calculations were performed to determine the aerodynamic drag forces exerted on the runners. Secondly, we estimated the metabolic savings for each of the runner’s positions in the pack of pacers. Finally, we estimated a potential equivalent running speed and a corresponding running time gain for each of the runner’s positions. Running second in a group of 5 runners would be the most effective drafting strategy, with a reduction of aerodynamic drag reaching 63.3%, corresponding to an improvement of 4.4% of the running economy. Furthermore, decreasing the drag forces acting on the runner would results in greater running speed. For example, a 63.3% reduction in the aerodynamic forces yields a 2.9% faster running speed (20.7 to 21.31 km/h) for an equal metabolic cost. Running in the wake of a leading runner (in a pack of five runners) over a marathon is estimated to provide a significant time saving of 3 min 28 s.
_eprint: https://doi.org/10.1080/14763141.2021.2006295
Keywords: CFD; drag force; mechanical power; metabolic power; performance; running